Detection Technologies of Laser Thermal Processing Quality - Yao, Yansheng; Yuan, Genfu; Yu, Zhen; Zhu, Shaofeng (Asian Journal of Chemistry, 2014)
The detection technology is valuable to the research and application of laser processing. The main test objects or content of three types of laser thermal processing (laser material removal, laser joining and laser surface modification of materials) is analyzed. The size precision, surface quality detection and the corresponding test equipment and methods are investigated. Some important instruments such as optical microscopy, acoustic microscopy, scanning electron microscopy, energy dispersive spectroscopy and X-ray diffraction, etc., especially their function and role in the laser processing are introduced. At last, some detection analysis works of laser processing in Anhui Jianzhu University are demonstrated.